DEVELOPMENT OF ENGLISH TEACHING MATERIALS FOR GUIDANCE AND COUNSELING STUDENT AT STATE UNIVERSITY OF MEDAN - Sirait, Albert Pauli; Rahmulyani, Rahmulyani; Lubis, Zuraidah (Universitas Negeri Medan, 2019)
The objectives of this study are (1) to know the English teaching materials taught in Guidance and Counselling at this time, (2) to know the skills needed by students in the Guidance and Counselling department in communication using English, (3) to know the English materials needed students to face the world of work, (4) the effectiveness of English language learning materials developed for improving students' English skills. The type of data obtained in the preliminary study is qualitative data and the results of the needs analysis of students' profile. This data is obtained by using interview and questionnaires. The type of data that results in the development of the model is qualitative data, which is the result of the validation of a team of experts; The results of individual test, and small group tests. The effectiveness test data is quantitative data. The results of this study are: (1) Descriptions of the needs of English language teaching materials, (2) Skills needed by students in communication using English, (3) English language teaching materials and (4) Effectiveness test results with T-Tests indicating that teaching materials English based on English for Specific Purposess developed in this field of research, effective; and the feasibility test of teaching materials shows the test results of 82, the results of the language feasibility test 87, the results of the feasibility test presentation 78, and the results of the feasibility test of decorative elements 75. It can be concluded that this ESP-based English teaching material is suitable for use in teaching materials that can improve students' ability to use English in academic and working activities.Keywords: ESP, Guidance and Counselling, Material.